Effect of Pressure Differences on Sludge Filtration Process Efficiency by Using Plate Filter Press - Saputri, Rizky Yunita; Nisa, Qurrotun A'yuni Khoirun; Yulianto, Mohamad Endy; Paramita, Vita (Journal of Vocational Studies on Applied Research, 2019)
Waste treatment in the industry produce sludge from the settling of solid material as a by product of the treatment process. The resulting sludge can’t be thrown away in large quantities because it can cause problems if there is still water content in it especially for industrial centers located around residential areas. So that filtration is carried out on the sludge from the Sedimentation Tub at the WWTP know in the area of Lamper, Semarang with the aim of reducing the volume of sludge by separating the water from the sludge before being discharged. The results of the analysis of the sludge filtration in the Settling Basin at WWTP obtained the value of cake resistance at a pressure of 75 kg / m2 of 4.42E + 11 m/kg, at a pressure of 90 kg/m2 of 5.62E + 11 m/kg and at a pressure of 104 kg/m2 of 6.74E + 11 m/kg. The results of the analysis on the resistance value of the filter medium obtained a value of 1.59E+12m-1 at a pressure of 75 kg/m2, 1.23E+12 m-1 at a pressure of 90 kg/m2 and 1.61E+12 m-1 at a pressure of 104 kg/m2. While in the analysis of water content, at a pressure of 75 kg/m2 obtained a value of 35.437%, at a pressure of 90 kg/m2 obtained a value of 35.024%, and at a pressure of 104 kg/m2 obtained a value of 34.024%. Efficiency The optimal pressure is 104 kg/m2.